Estrategias para la comprensión lectora en el área de lengua y literatura, bloque n°6 argumentación, en los niños y niñas del segundo grado de la escuela de educación básica Filomena Mora de Carrión del barrio San José, de la ciudad de Loja, período 2013-2014 - Gualán Gualán, Martha Alejandrina (2015)
The research on strategies for reading comprehension in the area of Language Arts Block No. 6 Argumentation, children in second grade, School of Basic Education Philomena theCarrion Mora San Jose neighborhood, city Loja period 2013-2014; overall objective was to contribute to strategies for reading comprehension, in the area of Language Arts Block No. 6 Argumentation in children of second grade PhilomenaCarrion Mora School of Barrio San José, City of Loja, 2013-2014. The research the descriptive and quasi–experimental. The methods used were, comprehensive, analytical, synthetic, participatory diagnosis, model or proactive, shop and evaluation as direct observation technique and application of a survey of teacher and students. In the research work intervened 35 human talents; one teacher and 34 students, thereof the following information was obtained; a large number of students disclosed that his teacher does not employ strategies for reading comprehension and most students report that their teacher if you use reading comprehension strategies in the educational process. We conclude that strategies for reading comprehension, form an essential part in education, achieving optimal student learning and hence their overall education.